Assessment of Accuracy of Death Certification in Teaching Hospital in A Developing Country - MUSHTAQ AHMED, MARIAM ARIF, SYED HAMAD RASOOL (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Death certification is largely random and fragmented in most developing countries. Objective: This study is done to evaluate errors in medical & non-medical part and to determine causes of errors of cause of death. Material and Method: Two hundred and twenty death certificates were randomly selected that have been issued from November 2013 to April 2014 for the deceased who were admitted in Services Hospital, Lahore. A predetermined error grading scale was used to assess the accuracy and completeness of selected death certificates. Causes of errors were analyzed and confirmed after detailed scrutiny of the medical section of death certificates. Data was statistically analyzed using SPSS version 20. Results: Four percent of death certificates were incompletely written.7% had no errors. The most frequent errors included Grade I errors involving patients’ demographics seen in 93% death certificates of which occupation was incorrect in 79.6% certificates. Grade IV and Grade V errors regarding cause/s of death were seen in 184(84%) and 128 (58%) certificates. Speculated causes of the errors of cause of death (99%) were lack of training and diagnostic incompetency. Conclusion: Errors in the completion of the death certificates are very common. Training for the doctors on induction to improve accuracy of death certificate is recommended during internship and at postgraduate level.